Narrative Ability in Autism and First-Degree Relatives. - Nayar, Kritika; Landau, Emily; Martin, Gary E.; Stevens, Cassandra J.; Xing, Jiayin; Sophia, Pirog; Guilfoyle, Janna; Gordon, Peter C.; Losh, Molly (Journal of Autism & Developmental Disorders, 2025)
Narrative is an important communication skill for sharing personal experiences and connecting with others. Narrative skills are often impacted in autism spectrum disorder (ASD) and have important consequences for social interactions and relationships. Subtle differences in narrative have also been reported among first-degree relatives of autistic individuals, suggesting that narrative may also be an etiologically important language-related skill that is influenced by genes associated with ASD. This study examined narrative ability and related visual attention during narration in ASD and first-degree relatives of individuals with ASD (siblings and parents) to understand how narrative and related attentional styles may be variably impacted across the spectrum of ASD genetic influence. Participants included 56 autistic individuals, 42 siblings of autistic individuals, 49 controls, 161 parents of autistic individuals, and 61 parent controls. Narratives were elicited using a wordless picture book presented on an eye tracker to record concurrent gaze. Findings revealed parallel patterns of narrative differences among ASD and sibling groups in the use of causal language to connect story elements and the use of cognitive and affective language. More subtle differences within the domain of causal language were evident in ASD parents. Parallel patterns in the ASD and sibling groups were also found for gaze during narration. Findings implicate causal language as a critical narrative skill that is impacted in ASD and may be reflective of ASD genetic influence in relatives. Gaze patterns during narration suggest similar attentional mechanisms associated with narrative among ASD families.